Cefiderocol: A Siderophore Cephalosporin. Issue 12 (December 2020) - El-Lababidi, Rania M.; Rizk, John George
Objective: This article reviews the available data on the chemistry, spectrum of activity, pharmacokinetic and pharmacodynamic properties, clinical efficacy, and potential place in therapy of cefiderocol. Data Sources: A literature search through PubMed, Google Scholar, and ClinicalTrials.gov was conducted (2009 to March 2020) using the search terms cefiderocol and S-649266 . Abstracts presented at recent conferences, prescribing information, and information from the US Food and Drug Administration (FDA) and the manufacturer's website were reviewed. Study Selection and Data Extraction: All relevant published articles, package inserts, and unpublished meeting abstracts on cefiderocol were reviewed. Data Synthesis: Cefiderocol is the first siderophore antibiotic to be approved by the FDA. It was shown to be active against a wide range of resistant Gram-negative pathogens, including multidrug-resistant (MDR) Pseudomonas aeruginosa, Acinetobacter baumannii, Enterobacteriaceae, and Stenotrophomonas maltophilia . Cefiderocol was studied in the treatment of adult patients with complicated urinary tract infections (cUTIs) and nosocomial pneumonia and was well tolerated. In a recently completed prospective study, higher mortality was observed with cefiderocol in the treatment of serious infections caused by carbapenem-resistant (CR) Gram-negative pathogens. Relevance to Patient Care and Clinical Practice: The approval of cefiderocol provides a new option in the treatment of cUTIs and potentially treatment of nosocomial pneumonia caused by resistant Gram-negative pathogens. Given the higher mortality observed with cefiderocol, its use in the treatment of CR Gram-negative infections should be carefully considered. Conclusion: Cefiderocol shows promising activity against MDR Gram-negative pathogens. Its use in the treatment of serious infections caused by CR Gram-negative bacteria needs further evaluation in phase III clinical studies.